Cu–(Ni–Co–Au)-bearing massive sulfide deposits associated with mafic–ultramafic rocks of the Main Urals Fault, South Urals: Geological structures, ore textural and mineralogical features, comparison with modern analogs - Melekestseva, I; Zaykov, V; Nimis, P; Tret'yakov, G; Tessalina, Svetlana (Elsevier Science BV, 2013)
Cu-rich massive sulfide deposits associated with mafic–ultramafic rocks in the southern portion of the Main Urals Fault (MUF) are characterized by variable enrichments in Ni (up to 0.45 wt.%), Co (up to 10 wt.%) and Au (up to 16 ppm in individual hand-specimens). The Cu (Ni–Co)-rich composition of MUF deposits, as opposed to the Cu (Zn)-rich composition of more eastward massive sulfide deposits of broadly similar age along the western flank of the Magnitogorsk arc, reflects the abundance of seafloor-exposed, Ni–Co-rich ultramafic rocks in the most external portion of the Early-Devonian Magnitogorsk forearc. Morphological, textural, and compositional differences between individual deposits are interpreted to be the result of the sulfide deposition style and, in part, of the original subseafloor lithology. One deposit produced by dominantly on-seafloor hydrothermal processes is characterized by pyrite–marcasite>>pyrrhotite, not so low Zn grades (occasionally up to 2 wt.%), abundant clastic facies and periodical superficial oxidation. Deposits produced by dominantly subseafloor hydrothermal processes are characterized by pyrrhotite>pyrite, very low Zn (generally < to << 0.1 wt.%), volumetrically minor clastic facies, and multi-layer deposit morphology. Very low Ni/Co ratios in the on-seafloor deposit may indicate a dominant metal contribution from a mafic rather than ultramafic source. The sulfide mineralization was associated with extensive hydrothermal alteration of the host ultramafic and mafic rocks, leading to formation of abundant talc, talc–carbonate and chlorite rocks.Occurrence of large volumes of such altered lithotypes in ophiolitic belts may be considered as a potential searching criteria for MUF-type (Cu, Co, Ni)-deposits. In spite of the contrasting geodynamic environment, geological, geochemical, textural and mineralogical peculiarities of the MUF deposits in many respects are similar to those of ultramafic-hosted massive sulfide deposits along the Mid-Atlantic Ridge. In geological time, supra subduction-zone settings appear to have been more effective than mid-ocean ridge settings for preservation of ultramafic-hosted massive sulfide deposits.